The virtual esophagus: investigating esophageal functions in silico. Issue 1 (16th June 2016) - Du, Peng; Yassi, Rita; Gregersen, Hans; Windsor, John A.; Hunter, Peter J.
Abstract : Esophageal and gastroesophageal junction (GEJ) diseases are highly prevalent worldwide and are a significant socioeconomic burden. Recently, applications of multiscale mathematical models of the upper gastrointestinal tract have gained attention. These in silico investigations can contribute to the development of a virtual esophagus modeling framework as part of the larger GIome and Physiome initiatives. There are also other modeling investigations that have potential screening and treatment applications. These models incorporate detailed anatomical models of the esophagus and GEJ, tissue biomechanical properties and bolus transport, sensory properties, and, potentially, bioelectrical models of the neural and myogenic pathways of esophageal and GEJ functions. A next step is to improve the integration between the different components of the virtual esophagus, encoding standards, and simulation environments to perform more realistic simulations of normal and pathophysiological functions. Ultimately, the models will be validated and will provide predictive evaluations of the effects of novel endoscopic, surgical, and pharmaceutical treatment options and will facilitate the clinical translation of these treatments.